The effects of game types on intensity of small-sided games among pre-adolescent youth football players - Halouani, J.; Chtourou, H.; Dellal, A.; Chaouachi, A.; Chamari, K. (Biology of Sport, 2017)
The aim of this study was to examine the effects of variations in pitch dimensions on pre-adolescent youth soccer players' physiological responses during two different types of small-sided games (SSG). Sixteen young soccer players (age: 13.2 ± 0.6 years; body mass: 52.5 ± 7 kg; height: 163.4 ± 6 cm) participated in this study. They performed 4 vs. 4 stop-ball SSG (SB-SSG) vs. small-goals SSG (SG-SSG) with 4×4 min and 2 min of passive recovery in between, using 3 different pitch sizes (small: 10×15, medium: 15×20, and large: 20×25 m). Heart rate (HR), lactate concentration ([La-]), and rating of perceived exertion (RPE) were measured during each session. The results show that SB-SSG induced higher HR responses than SG-SSG for the 3 pitch sizes: for HR (167.2±3.0 vs. 164.5±3.0, 172.3±2.9 vs. 169.2±3.1, and 175.4±3.1 vs. 171.1±2.7 bpm; P<0.05, for small, medium, and large, respectively) and [La-] (7.1±1.0 vs. 6.5±1.04, 7.3±1.0 vs. 6.8±1.2, and 7.8±0.9 vs. 7.1±0.8 mmoll-1; P<0.05 on small, medium, and large pitches, respectively), whereas RPE scores were significantly higher during SB-SSG compared to SG-SSG (6.2±1.0 vs. 5.8±0.9; P<0.05, respectively) on the small pitch. In the present study higher physiological responses were observed in SSG in pre-adolescent young soccer players when using the stop-ball conditions in comparison with the small-goal rule for all pitch sizes - small, medium, and large. Stopball conditions in comparison with the small-goal rule for all pitch sizes - small, medium, and large.